Repositioning the Teaching Profession to Meet Developmental Challenges in Nigeria - Ayodele, J. B.; Oyewole, B. K. (Mediterranean Journal of Social Sciences, 2012)
The issue of nation building and development is cardinal among the goals of any nation. In an attempt to meet the needs ofcitizens and also be in tune with other nations in a dynamic and globalised world, Nigeria is currently grappling with a lot of challenges.The place of the teaching profession in meeting these challenges cannot be overemphasized. This paper attempts to examine theconcept of development, developmental challenges of contemporary Nigeria, the place of the teaching profession, and recommendedstrategies for repositioning the teaching profession in Nigeria. It concludes that repositioning the teaching profession to meetdevelopmental challenges in Nigeria should be paramount in the mind of all stakeholders. The drive towards making Nigeria one of thetop developed economies in the world by year 2020 could be realized if teaching profession is highly recognized by the government.